Case report: The effect of second-line vebreltinib treatment on a patient with advanced NSCLC harboring the MET exon 14 skipping mutation after tepotinib treatment - Huang, Siyuan; Li, Linlin; Yan, Ningning; Zhang, Huixian; Guo, Qianqian; Guo, Sanxing; Geng, Di; Liu, Xincheng; Li, Xingya (Frontiers in Oncology, 2024)
Background: High selective type Ⅰb mesenchymal-epithelial transition gene (MET) tyrosine kinase inhibitors (TKIs) are the standard of care (SOC) therapy for previously untreated non-small cell lung cancer (NSCLC) harboring MET exon 14 (METex14) skipping mutations. However, there are rare reports describing effective regimens for patients who fail SOC without identifying resistant mutations or tissue transformation.We report the first case of a 74-year-old female with lung adenocarcinoma (cT1cNxM0) harboring METex14 splice region mutation, which was identified by a next-generation sequencing (NGS) based assay. The patient was administered two treatments, including first-line tepotinib and second-line vebreltinib. The patient achieved progression-free survival (PFS) of 7.6 months, and then disease progression of tepotinib was observed. A re-biopsy was performed for NGS, which revealed the same mutations as before, with no new gene mutations detected. The woman received subsequent vebreltinib therapy and experienced durable clinical benefits. In the first 6.8 months, chest computed tomography demonstrated stable disease. Then she achieved partial response (PR). The durable PR lasted for more than 13 months, and the PFS is currently over 20 months, exceeding the prior treatment.This case highlights the importance of considering re-biopsy and re-analysis of genetic profiles in NSCLC patients harboring METex14 skipping mutations after progressive disease in MET TKIs treatment. This raises the possibility that vebreltinib may have long-term survival benefits for patients without mutations conferring resistance. (Funded by Beijing Pearl Biotechnology Co., Ltd; ClinicalTrials.gov number, NCT04258033